Simple views on condensed matter - Gennes, Pierre-Gilles De (Singapore World Scientific, 1992)
This volume contains a selection of important papers by P-G de Gennes (1991 Nobel Prize Winner in Physics) which have had a long-lasting impact on our understanding of condensed matter (solid state physics, liquid crystals, polymers, interfaces, wetting and adhesion).
Includes bibliographies and index.
Keywords: Cơ bản